THE RELATIONSHIP OF THE DISTRIBUTION OF SEA SURFACE TEMPERATURE WITH RAINFALL AND WIND IN THE WATERS OF WEST SUMATRA - Azmiada, Zela; Elizal, Elizal; Mulyadi, Aras (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This research was carried out in February-March 2023 in the West Sumatra waters. It aimed to determine the variability of sea surface temperature, rainfall intensity, wind direction, and speed in the West Sumatra waters. Sea surface temperatures were taken from three stations, namely: in the coastal waters of Pariaman City, Padang-Pariaman Regency, and Bungus, Padang. The survey method was used, which was directly observed in the field. The results showed that the Sea Surface Temperature of the study areas ranged from 29.25oC-30.28oC, while the rainfall went from 211.97-499.89 mm, and the dominant speed was between 0.50-2.10 m/s. The correlation analysis between rainfall and sea surface temperatures in Station 1 yielded an